Cross-sectional study on patient-physician aggression in Belgium: physician characteristics and aggression types. Issue 12 (18th December 2019) - De Jager, Lennart; Deneyer, Michel; Buyl, Ronald; Roelandt, Sophie; Pacqueu, Ralph; Devroey, Dirk
Abstract : Objectives: The aim of this Belgian research study was to describe the characteristics of physicians who are at increased risk for patient-physician aggression. Second, aggression subtypes were described and data were provided on the prevalence of patient-physician aggression in Belgium. Design: Cross-sectional survey. Setting: Primary and secondary care inside and outside hospitals. Participants: Any physician who had worked in Belgium for the preceding 12 months was eligible to participate (n=34 648). Main outcome measures: An online, original questionnaire was used to obtain physician characteristics (eg, age, sex, native language), department, working conditions and contact with aggressive patients during their career and during the preceding 12 months. Results: The questionnaire was completed by 4930 participants and 3726 (76%) were valid to take into account for statistics. During the preceding 12 months, 37% had been victims of aggression: 33% experienced verbal aggression, 30% psychological, 14% physical and 10% sexual. Multiple answers were allowed. Women and younger physicians were more likely to experience aggression. Psychiatric departments and emergency departments were the settings most commonly associated with aggression. Physicians who provided primarily outpatient care were more subject to aggression. Conclusion: Belgian physicians experience several forms of aggression. Those most at-risk of aggression are young and female physicians who work in outpatient, emergency or psychiatric settings.